FORMULATION AND EVALUATION OF COLON TARGETED MATRIX TABLETS OF IBUPROFEN - Ramanathan, M; Subramanian, L; varghese, Bency Susan (Asian Journal of Pharmaceutical Research and Development, 2018)
Ulcerative colitis is a chronic condition of inflammation and ulcers in colon and rectum, the present study aim was to developed Ibuprofen colon targeted matrix tablet for the effective treatment of Ulcerative colitis. Formulation of Ibuprofen matrix tablets was prepare by using different polymers such as Eudragit S 100 and Ethyl cellulose (as carriers) in different ratios. Ibuprofen tablet were prepared by direct compression method. Based on FT-IR study drug and excipient compatibility was checked and confirmed the nil interactions. The prepared tablets were coated with an enteric polymer and were evaluated for the physicochemical parameters such as hardness, thickness, content uniformity, drug content and in vitro-drug release studies. Among the six formulation F6 showed better drug release 98.51% of Ibuprofen. The stability study was also conducted, the results showed there is no significant changes of drug content and other parameter, which make a clearance of Ibuprofen matrix tablet formulation.